2010
DOI: 10.1007/s12011-010-8625-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Oxidative Profile in Graves’ Disease, Hashimoto’s Thyroiditis, and Papillary Thyroid Cancer

Abstract: The aim of this study was to evaluate and compare the oxidative profiles of three thyroid disorders: Graves' disease (GD), Hashimoto thyroiditis (HT), and papillary thyroid cancer (PTC). Malondialdehyde levels (MDA), glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) activities were examined in the plasma of 52 patients (29 untreated HT, 16 untreated GD, and 7 PTC who underwent surgical therapy). Results were compared with those of 30 healthy controls and among the three groups of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 29 publications
7
47
2
1
Order By: Relevance
“…While there have been some which report decreased activity [29], most studies demonstrate increased levels [26,30,31]. Our results support neither view, as we could not find any significant change in plasma SOD levels in patients compared to controls.…”
Section: Discussioncontrasting
confidence: 47%
“…While there have been some which report decreased activity [29], most studies demonstrate increased levels [26,30,31]. Our results support neither view, as we could not find any significant change in plasma SOD levels in patients compared to controls.…”
Section: Discussioncontrasting
confidence: 47%
“…Evidently, free radicals are involved in the physiological and pathological processes in the thyroid gland (13,14). According to previous studies, thyroid cancer is associated with enhanced oxidative stress (15,16).…”
Section: Discussionmentioning
confidence: 94%
“…5 Lassoued et al found that the plasma MDA level significantly increased in Hashimoto thyroiditis patients. 19 Torun et al found elevated lipid peroxidation in both overt hypothyroidism and subclinical hypothyroidism patients. 7 All data on MDA and Hashimato thyroidits reported in the literature cited above were derived from Hashimoto thyroiditis patients who were not on levothyroxine treatment and knowledge on MDA and Hashimoto thyroiditis patients treated with levothyroxine is limited in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…25 Lassoued et al found that plasma SOD levels significantly increased in Hashimoto thyroiditis patients. 19 All the findings mentioned above were derived from studies carried out in Hashimoto thyroiditis patients who were not on treatment. Only Baskol et al, Gerenova and Gadjeva reported on the differences in SOD levels both before and after levothyroxine treatment.…”
Section: Discussionmentioning
confidence: 99%